Peran Komunikasi Interpersonal dalam Meningkatkan Efektivitas Kerja Tim di Era Digital - Sanmas, Masni; Qadir, Abdul; Nahria, Nahria; Laili, Izzatul (Neolectura, 2023)
This study explores the role of interpersonal communication in enhancing team work effectiveness in the digital era, focusing on how effective communication practices can strengthen mutual understanding, coordination, and collaboration within teams. Utilizing a qualitative method and literature review, this research collected and analyzed data from various contemporary sources to comprehend the dynamics of interpersonal communication within the context of technology-supported team work. The findings indicate that interpersonal communication characterized by openness, empathy, and support not only strengthens relationships among team members and builds trust but also reduces misunderstandings and conflicts. Furthermore, the study highlights the importance of training in interpersonal communication skills to bolster team cooperation and expedite the collaboration process by leveraging appropriate digital communication tools. These findings underscore the significance of effective interpersonal communication strategies and the integration of digital communication technology to create a productive and harmonious work environment, as well as to improve job satisfaction, motivation, and employee retention in the digital era.